Experimental investigation and striation study of Inconel 718 by using abrasive water jet drilling. (2022) - Rajesh, M.; Vijayakumar, R.; Rajkumar, K.; Ramraji, K.
Abstract: Abrasive waterjet (AWJ) technology is a viable production method for machining metal matrices with its own set of benefits. AWJD is a fantastic option for Despite its higher cost, the metal matrix is increasingly being used in many applications such as space, aviation, marine, architecture, and automobiles because of its superior physical and mechanical characteristics AWJ drilling of Inconel 718, on the other hand, has several drawbacks. The striation angle quality and surface morphology/integrity were investigated in this study. Inconel 718 material is waterjet drilled under various operating circumstances. The impact of a few essential variables affecting striation angle (SA) by using parameters traverse speed (TS), jet pressure (JP), gap distance (Sod). The replies for every trials designed according to Taguchi's L9 orthogonal array revealed the characteristics of striation angle. The characteristic change is tabulated, and a graph is presented using Grey Relation Analysis (GRA) and ANOVA.